2004
DOI: 10.1086/381295
|View full text |Cite
|
Sign up to set email alerts
|

Empirically Constrained Color-Temperature Relations. II.uvby

Abstract: A new grid of theoretical color indices for the Strömgren uvby photometric system has been derived from MARCS model atmospheres and SSG synthetic spectra for cool dwarf and giant stars having À3:0 ½Fe=H þ0:5 and 3000 T eA 8000 K. At warmer temperatures (i.e., 8000 < T eA 40; 000 K), this grid has been supplemented with the synthetic uvby colors from recent Kurucz atmospheric models without overshooting (Castelli, Gratton, & Kurucz, published in 1997). Our transformations appear to reproduce the observed colors… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
113
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(120 citation statements)
references
References 73 publications
(73 reference statements)
7
113
0
Order By: Relevance
“…We note in passing that Clem et al (2004) also found discrepancies between their calculated m 1 indices and observations. For their coolest models they had to apply upward corrections to their calculated m 1 indices of 0.1-0.3 mag.…”
Section: The Metallicity Calibrationmentioning
confidence: 57%
See 3 more Smart Citations
“…We note in passing that Clem et al (2004) also found discrepancies between their calculated m 1 indices and observations. For their coolest models they had to apply upward corrections to their calculated m 1 indices of 0.1-0.3 mag.…”
Section: The Metallicity Calibrationmentioning
confidence: 57%
“…15, the CN line strengthening which is expected for the red giants improves the fit to observed c 1 indices for the red giant models considerably. Clem et al (2004) applied semiempirical corrections also to their calculated (u − v) and (v − b) colours in order to fit observations. The resulting effect on their c 1 indices is typically less than 0.1 mag while we would need a downward correction of our c 1 indices of about 0.2 mag for the coolest models to fit (cf.…”
Section: Surface-gravity Calibrationmentioning
confidence: 99%
See 2 more Smart Citations
“…Colors are based on calibrations from ATLAS-9 spectra (Castelli & Kurucz 2003). Small but systematic differences are not surprising and are partly due to the isochrone calibration itself (see Clem et al 2004).…”
Section: Cluster Agementioning
confidence: 99%